Comb‐like polymer with sulfo groups and its dispersion and rheological properties in aqueous ceramic suspensions. Issue 10 (7th November 2016) - Zhu, Yinhui; Fang, Ying; Min, Yahong; Huang, Xiaojun; Li, Wensheng; Yuan, Jianmin; Wang, Shuangyin; Wu, Zhenjun
ABSTRACT: Two types of new comb‐like polymers were formed as dispersants for aqueous ceramic suspensions with isoprenyloxy poly(ethylene glycol ether), acrylic acid, maleic anhydride as the main starting materials. During the synthesis, one comb‐like polymer introduced sodium methylallyl sulfonate (SMAS) into the reaction media, whereas the other did not. The chemical structure and molecular weight were characterized by Fourier transform infrared spectroscopy and gel permeation chromatography. The effects of the polymers on the dispersion, ζ potential and rheological properties of the kaolin suspensions are discussed in detail. The results indicate that SMAS facilitated chain transfer, controlled the effective charge density of the surface, and increased the electrostatic repulsion force. The kaolin suspensions displayed shear‐thinning behavior on the basis of the electrostatic and steric effects of the comb‐like polymers. The apparent viscosity decreased from 1088 to 258 mPa s with the assistance of the SMAS‐prepared comb‐like polymer as a dispersant. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44563. Abstract :